On the Absolute Summability Factors of Infinite Series involving Quasi-f-power Increasing Sequence (Journal of Informatics and Mathematical Sciences, 2012)
In this note we improve a result concerning absolute summability factor of an infinite series via quasi $β$-power increasing sequence achieved by Sevli and Leindler [1].
Keywords: Infinite series; Absolute summability; Summability factor